N-/T-Type vs. L-Type Calcium Channel Blocker in Treating Chronic Kidney Disease: A Systematic Review and Meta-Analysis - Mingming Zhao; Ziyan Zhang; Zhiyu Pan; Sijia Ma; Meiying Chang; Jiao Fan; Shunxuan Xue; Yuejun Wang; Hua Qu; Yu Zhang (MDPI AG, 2023)
Renin-angiotensin system (RAS) inhibitors and calcium channel blockers (CCB) are often used together in chronic kidney disease (CKD). The PubMed, EMBASE, and Cochrane Library databases were searched to identify randomized controlled trials (RCTs) in order to explore better subtypes of CCB for the treatment of CKD. This meta-analysis of 12 RCTs with 967 CKD patients who were treated with RAS inhibitors demonstrated that, when compared with L-type CCB, N-/T-type CCB was superior in reducing urine albumin/protein excretion (SMD, −0.41; 95% CI, −0.64 to −0.18; p < 0.001) and aldosterone, without influencing serum creatinine (WMD, −3.64; 95% CI, −11.63 to 4.35; p = 0.37), glomerular filtration rate (SMD, 0.06; 95% CI, −0.13 to 0.25; p = 0.53), and adverse effects (RR, 0.95; 95% CI, 0.35 to 2.58; p = 0.93). In addition, N-/T-type CCB did not decrease the systolic blood pressure (BP) (WMD, 0.17; 95% CI, −1.05 to 1.39; p = 0.79) or diastolic BP (WMD, 0.64; 95% CI, −0.55 to 1.83; p = 0.29) when compared with L-type CCB. In CKD patients treated with RAS inhibitors, N-/T-type CCB is more effective than L-type CCB in reducing urine albumin/protein excretion without increased serum creatinine, decreased glomerular filtration rate, and increased adverse effects. The additional benefit is independent of BP and may be associated with decreased aldosterone (PROSPERO, CRD42020197560).